Pengaruh Minat dan Kecerdasan Emosional Terhadap Hasil Belajar IPS Siswa Menggunakan Metode Flipped Classroom - Reflianto, Reflianto; Ariani, Farida; Afnita, Nora; Wandi, Joni Indra (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
The success of student learning during class learning is greatly influenced by interests and emotional intelligence so that teachers must understand students' learning needs and the factors that influence them. This study investigates the effect of learning interest and emotional intelligence on students' learning outcomes. The research employed a quantitative approach using survey methods and a cross-sectional design. The study population consisted of all seventh-grade students at SMP Negeri 2 Kota Pariaman, from which a sample of 40 students was selected using simple random sampling. The research instruments included a Likert-scale questionnaire to measure learning interest and emotional intelligence, and academic records to assess learning outcomes. Data were analyzed using simple and multiple regression analyses with SPSS version 25. The results indicated a significant positive effect of both learning interest and emotional intelligence on students' learning outcomes in social sciences. It is recommended that seventh-grade social studies teachers assess students' learning interests and emotional intelligence before instruction. This will enable adapting teaching methods to better meet students' needs and enhance learning outcomes